A Study on Lymphoblastic Leukemia Using Image Processing - Firdous, Afsheen; Ramana, Kompella Venkata (International Journal of Computer Sciences and Engineering, 2020)
Blood cancer is one of the types of cancer. Leukemia is one among them. Which was caused due to the abnormal growth of the white blood cells in the bone marrow in the blood. This also affects the functionality of the white blood cells and the red blood cells, platelets. The leukaemia is further divided into four types. In this paper, we are going to discuss and examine the results of the acute lymphoblastic leukemia. In the phase of segmentation procedure, we have taken the edge-based segmentation. Here we will see the results by applying the median filter once and twice with different masks along with different operators. For the process, we have done it in processing tool like Pycharm with python, Opencv package. We have observed the difference between the operators with its functionality, changing the mask values for filtration. The good segmentation leads to the accuracy in classification.